Sub-task 5.2.1: Overall framework of TDS Processes. D5.3 Generic flowcharts and interrelations with CCPs and Indicator - Pité, Marina (2015)
FP7 - This project has received funding from the European Union’s Seventh Framework Programme for research, technological development and demonstration (Grant Agreement no. 289108)